Pregnancy Outcomes of Different Endometrial Preparation in Patients With a History of Cesarean Section - Gan, Run Xin; Li, Yuan; Song, Juan; Wen, Quan; Lu, Guang Xiu; Lin, Ge; Gong, Fei (Frontiers in Endocrinology, 2022)
Objective: To investigate the efficacies of three cycle regimens in women receiving frozen embryo transfer with a history of cesarean section: natural cycle treatment, hormone replacement therapy and treatment with gonadotropin-releasing hormone agonist. Design: Retrospective cohort study. Methods: patients (N = 6,159) with a history of caesarean section who fulfilled the inclusion criteria were enrolled in the study from January 2014 to December 2019 at the CITIC-Xiangya Hospital of Reproduction and Genetics. Reproductive outcomes of patients in the natural cycle (n = 4,306) versus hormone replacement therapy (n = 1,007) versus gonadotropin-releasing hormone agonist + hormone replacement therapy groups (n = 846) were compared. Continuous data were analyzed using Student’s t-test, and categorical variables were analyzed using the χ2 test. Multivariable logistic regression was used to evaluate the possible relationships between the types of endometrial preparation and pregnancy outcomes after adjusting for confounding factors. Results: The unadjusted odds of the miscarriage rate of singleton pregnancies were significantly higher in the hormone replacement therapy compared with the natural cycle (25.5% versus 20.4%, respectively). After adjusting for possible confounding factors, the early miscarriage rate and the miscarriage rate of singleton pregnancies remained significantly higher in the hormone replacement therapy than the natural cycle. The clinical pregnancy rates in the natural cycle, hormone replacement therapy and gonadotropin- releasing hormone agonist + hormone replacement therapy of women with a history of cesarean section was 48.8%, 48% and 47.1%, respectively, and the live birth rates were 37%, 34.1% and 35.7%, respectively. Conclusions: In women undergoing frozen embryo transfer with a history of cesarean section hormone replacement therapy for endometrial preparation was associated with a higher early miscarriage rate, albeit after statistical adjustment for confounding factors. However, the risk observed was little and did not influence the overall reproductive performances.